2018
DOI: 10.1097/rli.0000000000000479
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Safety Guidelines on the Use of Iodinated Contrast Material

Abstract: Postcontrast incidences of CIN and mortality at 35 days are significantly higher in the population with eGFR <30 mL/min/1.73 m than in the former high-risk population with eGFR 30 to 59 mL/min/1.73 m, even after prophylactic intravenous hydration. The risk of complications of prophylactic intravenous hydration is similar and substantial in both populations. Obtaining evidence from a randomized trial that efficacy of prophylactic intravenous hydration outweighs the risk of complications is important but may not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 44 publications
0
40
0
6
Order By: Relevance
“…An analysis of patients with eGFR < 30 mL/min/1.73 m 2 excluded from the AMACING trial showed that these patients represent a different, more vulnerable population to those with eGFR 30-59 mL/min/1.73 m 2 included in the trial [23]. Incidences of post-contrast adverse events were substantially higher in the eGFR < 30 mL/min/1.73 m 2 population compared to those in the AMACING trial population: CIN 13.6% versus 2.7% (p = 0.0019); 1 month dialysis 0.9% versus 0.0% (p = 0.2646); and 1 month mortality 9.2% versus 0.0% (p < 0.0001).…”
mentioning
confidence: 99%
“…An analysis of patients with eGFR < 30 mL/min/1.73 m 2 excluded from the AMACING trial showed that these patients represent a different, more vulnerable population to those with eGFR 30-59 mL/min/1.73 m 2 included in the trial [23]. Incidences of post-contrast adverse events were substantially higher in the eGFR < 30 mL/min/1.73 m 2 population compared to those in the AMACING trial population: CIN 13.6% versus 2.7% (p = 0.0019); 1 month dialysis 0.9% versus 0.0% (p = 0.2646); and 1 month mortality 9.2% versus 0.0% (p < 0.0001).…”
mentioning
confidence: 99%
“…The first study, detailed in chapter 5, was carried out on the prospectively screened patients with eGFR <30 ml/min/1.73m 2 excluded from the AMACING trial. 128 The aim was to look at the implicit assumptions underlying the guideline update in the recommendation for prophylactic intravenous hydration: 1) patients with eGFR <30 ml/min/ 1. In the discussion of the article, feasibility of carrying out a randomised controlled trial similar to AMACING in this population was assessed.…”
Section: Research-focusmentioning
confidence: 99%
“…71,73,76,78 These patients represent 0.1% to 0.5% of the general population 130,167,168 and 0.05% to 1.8% of patients undergoing elective contrast procedures. 128,147,151,166 The estimated incidences of post contrast adverse events in this population combined with the low availability of patients makes randomised trials with sufficient power unrealistic. 128 A few observational studies on post contrast outcomes in patients with eGFR less than 30 ml/min/1.73m 2 were recently published, however, and these may offer some insight.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations